Effects of TanDEM-X Acquisition Parameters on the Accuracy of Digital Surface Models of a Boreal Forest Canopy. Issue 2 (4th March 2017) - Sadeghi, Yaser; St-Onge, Benoît; Leblon, Brigitte; Simard, Marc
ABSTRACT: The accuracy of digital surface models (DSMs) derived from TanDEM-X interferograms of a dense and mostly evergreen boreal forest area was evaluated across 5 datasets acquired under various geometrical and phenological conditions. For each, an interferometric synthetic aperture radar (InSAR) canopy height model (CHM) was produced by subtracting a LiDAR digital terrain model from the TanDEM-X DSM. These InSAR CHMs were compared to a LiDAR CHM at a resolution of 25 m and led to biases from 0.77 to 1.56 m, r 2 from 0.68 to 0.38, and root-mean-square errors (RMSEs) from 2.06 to 3.67 m. Two datasets acquired in similar conditions differed by 1.27 m (RMSE). Differences in the interferometric baseline had the strongest effect on the DSMs (RMSE of 3.27 m between short and long baseline DSMs). The height of ambiguity therefore had a significant effect on the resulting canopy height. The effect of phenological changes on canopy height estimations was lower (RMSE of 2.30 m between leaf-on and leaf-off DSMs) and not highly significant. These results indicate that, despite variations in the acquisition conditions, a continuous TanDEM-X mosaic acquired with proper baselines could produce a reliable estimate of canopy surface elevations of evergreen closed-canopy boreal forests.